2021
DOI: 10.1016/j.ajem.2021.03.083
|View full text |Cite
|
Sign up to set email alerts
|

On-admission anemia predicts mortality in COVID-19 patients: A single center, retrospective cohort study

Abstract: Objectives We investigated the impact of anemia based on admission hemoglobin (Hb) level as a prognostic risk factor for severe outcomes in hospitalized patients with coronavirus disease 2019 (COVID-19). Methods A single-center, retrospective cohort study was conducted from a random sample of 733 adult patients (age ≥ 18 years) obtained from a total of 4356 laboratory confirmed SARS-CoV-2 cases who presented to the Emergency Department of Montefiore Medical Center betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 27 publications
(26 reference statements)
9
45
1
Order By: Relevance
“…In regard to risk factors for COVID-19 related severity, the only variable that held up to MVA for the outcome of hospitalization was admission Hb; this is consistent with previous findings of a significant Hb decrease from baseline for SCD patients requiring hospitalization [1] and studies that reported Hb as a strong predictor of COVID-19 related severity or mortality in the general population [16] , [24] , [25] For the outcome of ICU admission, 3 variables remained significant in the MVA: HCW employment, HU use, and immature granulocyte count on admission. HCW employment has not been previously reported as a risk factor in SCD ICU admission but has been associated with COVID-19 morbidity in the general US population as well as comprehensive meta-analysis [13] , [14] .. HU use has been reported to reduce morbidity in SCD in one report [1] but not others [10] , [21] .…”
Section: Discussionsupporting
confidence: 88%
“…In regard to risk factors for COVID-19 related severity, the only variable that held up to MVA for the outcome of hospitalization was admission Hb; this is consistent with previous findings of a significant Hb decrease from baseline for SCD patients requiring hospitalization [1] and studies that reported Hb as a strong predictor of COVID-19 related severity or mortality in the general population [16] , [24] , [25] For the outcome of ICU admission, 3 variables remained significant in the MVA: HCW employment, HU use, and immature granulocyte count on admission. HCW employment has not been previously reported as a risk factor in SCD ICU admission but has been associated with COVID-19 morbidity in the general US population as well as comprehensive meta-analysis [13] , [14] .. HU use has been reported to reduce morbidity in SCD in one report [1] but not others [10] , [21] .…”
Section: Discussionsupporting
confidence: 88%
“…(C) A defined set of anemia and kidney-related laboratory test measurements were compared between the PCH and PCNH cohorts in the pre-COVID and SARS-CoV-2 + intervals. iScience Article been suggested as biomarkers for mortality and disease severity in patients with COVID-19 (Chan et al, 2021;Faghih Dinevari et al, 2021;Hariyanto and Kurniawan, 2020;Nadim et al, 2020;Oh et al, 2021). However, our previously mentioned NLP analysis was the first to associate anemia with the long COVID syndrome and rehospitalization after SARS-CoV-2 clearance.…”
Section: Introductionmentioning
confidence: 84%
“…For example, the levels of albumin, hemoglobin, the mean platelet volume, and inflammatory markers (monocyte to eosinophil or neutrophil to lymphocyte ratios) are prognostic markers in patients with COVID-19 ( 17 19 ). In particular, anemia has been shown to be an independent predictor of mortality in COVID-19 patients ( 20 22 ). Therefore, we hypothesized that the inclusion of inflammatory and hematological markers would modulate the associations of obesity and hyperglycemia with death and ICU admission.…”
Section: Introductionmentioning
confidence: 99%